A novel approach to synthesize ultrasmall Cu doped Zn-In-Se nanocrystal emitters in a colloidal system - Ke, J.; Li, Xin Yong; Zhao, Q.; Shi, Y.; Chen, G. (Royal Society of Chemistry, 2014)
A facile phosphine-free approach is presented to prepare Cu doped ternary Zn–In–Se nanocrystals with high performance photoluminescence. By doping during nucleation stage, Cu dopant serving as a dominative emission centre was introduced into a weak fluorescence ternary system to modify the emission path. As a result of varying the ratios of zinc to indium, emission of the products is tunable ranging from 620 to 545 nm and a photoluminescence quantum yield of up to 20%. Meanwhile, a large Stokes shift of 467 meV is achieved.